The Irrationality of Malay Proselytisation : The Failure of Education as a Tool for “Civilising” Native - Sharifah Sophia, Wan Ahmad (Penerbit USM, 2022)
Abstract. Critiques of imperialism tend to focus on the motivations of empire-builders located at the metropolitan. However, seeing from the vantage of the women and men in the colonies, realities were often more tragic. The present article seeks to test a proposition pertaining to the irrationality of colonialism by examining the Anglican missionary work in education used as a tool for evangelising Malay society in Sarawak. The correspondence by the mission’s leader Bishop Francis Thomas McDougall (1817– 1886) to the missionary societies in England, namely, the Borneo Church Mission and the Society for the Propagation of the Gospel in Foreign Parts, constitutes the main source-material informing the argument on the irrational motivation that drove the proselytising activity in the mid-19th century Sarawak. Utilising the concept “El Dorado”, it is argued that the subterranean facets of fantastical dream, ungrounded hope and fanatical imagination produced real-life disillusionment for the historical agents carrying out the dystopian programme of civilising Malay and other natives. It is found that the proselyting mission had failed to succeed because it was predicated on the intolerance of religious difference and the compulsion to subdue it. The article concludes by reiterating a perspective that considers irrational motive as a significant historical force.